Pendugaan Potensi Volume Akuifer Menggunakan Metode Geolistrik di Pulau Gili Ketapang, Probolinggo, Jawa Timur - Pryambodo, Dino Gunawan; Prihantono, Joko (EKSPLORIUM, 2019)
Geoelectric measurement using Schlumberger configuration was carried out in Gili Ketapang Island, a small island with a population density of 12,356 people/km2. The measurement conducted at 8 locations using a vertical electrical sounding (VES) method. The result of geoelectric data processing shows aquifer resistivity value ranging from 2.71–206 Ωm at the sandy limestone lithology. The largest aquifer volume potency based on the 2D groundwater aquifer model is in the K-03 and K-17 location. The 3D groundwater aquifer model shows that the aquifer volume is 27,689,400 m3 or about 27.689.400.000 liters. The groundwater inside the aquifer will last within 68 years in a condition where there is no population increase. Besides, the groundwater also lasts even there is no water addition inside the aquifer, by natural or artificial